Age-related evaluation of skin barrier parameters in retrievers - Lee, Eun-Hae; Yoo, Dongkuk; Lee, Ju-Ri; Kim, Ji-Seon; Han, Hyun-Jung; Hyun, Jae-Eun (Frontiers in Veterinary Science, 2026)
IntroductionA disruption in the skin barrier, which serves as the primary defense against external pathogens, can lead to skin disorders. In humans, various factors influence the skin barrier, including age and anatomical site. Research on the canine skin barrier is limited; this study evaluated its function across age groups and anatomical sites in healthy retrievers.MethodsForty-five healthy retrievers were included and divided into three age groups: young (2–3 years, n = 15), middle-aged (4–6 years, n = 15), and old (7–8 years, n = 15). The skin barrier parameters, including pH, transepidermal water loss (TEWL), skin hydration, sebum, and surface temperature, were measured at the ear pinnae, axillae, and inguinal region. Statistical analyses were used to compare parameters by age and site and to assess correlations between them.ResultsSkin hydration significantly decreased with age at all anatomical sites. The pH and sebum levels varied by site, with the inguinal region showing the highest pH value and the pinnae showing the highest sebum and hydration levels. Negative correlations were found between TEWL and hydration and between TEWL and sebum. Meanwhile, positive correlations were observed between TEWL and temperature and between sebum and hydration.ConclusionSkin hydration decreased with age and varied by anatomical site. The pH and sebum levels showed site-specific differences. The significant correlations between parameters highlight physiological interactions in skin barrier function. These baseline data provide a useful reference for dermatological evaluation and a foundation for future studies on canine skin barrier physiology.